The Porphyromonas gingivalis hemagglutinins HagB and HagC are major mediators of adhesion and biofilm formation. (4th February 2016) - Connolly, E.; Millhouse, E.; Doyle, R.; Culshaw, S.; Ramage, G.; Moran, G.P.
Summary: Porphyromonas gingivalis is a bacterium associated with chronic periodontitis that possesses a family of genes encoding hemagglutinins required for heme acquisition. In this study we generated Δ hagB and Δ hagC mutants in strain W83 and demonstrate that both hagB and hagC are required for adherence to oral epithelial cells. Unexpectedly, a double Δ hagB /Δ hagC mutant had less severe adherence defects than either of the single mutants, but was found to exhibit increased expression of the gingipain‐encoding genes rgpA and kgp, suggesting that a Δ hagB /Δ hagC mutant is only viable in populations of cells that exhibit increased expression of genes involved in heme acquisition. Disruption of hagB in the fimbriated strain ATCC33277 demonstrated that HagB is also required for stable attachment of fimbriated bacteria to oral epithelial cells. Mutants of hagC were also found to form defective single and multi‐species biofilms that had reduced biomass relative to biofilms formed by the wild‐type strain. This study highlights the hitherto unappreciated importance of these genes in oral colonization and biofilm formation.